Human Capital's importance in Initial Coin Offerings' (ICOs) success - Campino, J.; Brochado, A.; Rosa, Á. (Economics Bulletin, 2020)
The Initial Coin Offerings (ICOs) are an emerging topic in the literature with several gaps still to fulfill. The ICOs have increased its importance not only due to the interest they have been raising but also due to the capital amounts involved in the projects, the innovative solutions they offer and the challenges they pose to regulators. There is some research on the ICOs' success factors but there is still no common measure of success as well as not many researches focused on the human capital importance for the projects success. In our research we will perform a literature review on the ICOs' topic and develop an econometric model with a database composed by 3158 profiles and 340 ICO projects in the banking/financial sector. We will be focusing on the human capital importance in these projects and propose three measures for project's success. With our research we intend to complement the literature on the ICOs projects and shed some light on the factors driving their success.